“The United Family“. The View of the Village of the Recovered Territories in the Literature of Ziemia Lubuska - Mikołajczak, Małgorzata (Slavia Occidentalis, 2014)
“The United Family” is a title of one of the novels by Zygmunt Trziszka published in 1965 as “The Great Pigsticking”, that made writer’s debut and initiated the rural theme in the literature of Ziemia Lubuska. Since 1965 Trziszka, considered as one of the most eminent regional writers, had written many novels and stories focused on the same topic: a village located on the Polish Recovered Territories. As a consequence, his prose output, presenting a wide spectrum of Polish post-war rural problems, gives the base local narrative and creates the identity of a new region and its community which was in the state of establishing itself and – most of all – the identity of immigrants settled in this area after World War II. Ziemia Lubuska, in contradistinction to the other Polish regions, wasn’t an industry-developed, where area and the agrarian culture prevailed over urban culture, and that’s why the rural subjects became were so popular here. The second reason for favouring this theme in post-war literature of Ziemia Lubuska, was a propaganda concept, so-called “western subject” in Polish culture – in the first post-war decades it concerned all rural issues (it was changed after political transformation and since 1989 the urban theme became more interesting to the Polish western writers). That’s why I concentrate mostly on the literature of the 60’s and 70’s. It was just the beginning of Lubuska literature. The aim of my paper is to give an outline of Trziszka’s work and other writers’ who followed him, and to picture of Lubuska village, created both in accordance with propaganda pressure and the expatriates’ and settlers’ expectations. I would like to take a closer look at the view shaped mainly by two literary traditions: the epos and the arcadian idea. The purpose of long narrative poem, announced by Polish cultural policy in 1959, and taken over by western writers, was to recount the deeds by heroic pioneer settlers’ deeds and to describe the process of after-war establishing the community (community unified as “one family”). Similar to the Arcadian as the dream of people living peacefully together in a beautiful landscape and in harmony with nature, that was attractive and helpful in the process of assimilation. Yet the literary image of Lubuska village was not only composed by these two crucial features, but also by subversive narrative, painting the strange, unpleasant and even damned land – a portrait, I would also devote attention to.